Dampak Alih Fungsi Lahan Sawah ke Kolam Ikan Air Tawar terhadap Pendapatan Petani di Kecamatan Padang Gelugur, Kabupaten Pasaman - Lamsyariah, Lamsyariah; Hermon, Dedi; Andrian, Andrian (YASIN, 2024)
This research aims to investigate two main aspects in Padang Gelugur Subdistrict, Pasaman Regency: first, the change in paddy field area into fish ponds from 2017 to 2022; second, to analyze the factors influencing this land conversion. The research method used is a mixed methods approach, which integrates quantitative and qualitative data to answer research questions related to behavior, social, and health aspects. The research results indicate that during the period from 2017 to 2022, approximately 144 hectares of paddy fields were converted into fish ponds. The main factors driving the community to undertake this land conversion include the significant income difference between paddy harvests and fish ponds, with income from fish ponds tending to be higher. Additionally, educational factors and weather conditions also play a significant role, particularly as Padang Gelugur Subdistrict frequently experiences high rainfall intensity, which can lead to flooding and crop failure.